EMILIN3, an extracellular matrix molecule with restricted distribution in skin. Issue 5 (2nd March 2017) - Corallo, Diana; Schiavinato, Alvise; Bizzotto, Dario; Milanetto, Martina; Guljelmovic, Marija; Keene, Douglas R.; Sengle, Gerhard; Braghetta, Paola; Bonaldo, Paolo
Abstract: EMILIN3 is an extracellular matrix glycoprotein that displays a dynamic and restricted expression pattern in connective tissues during post‐natal life. In this study, we report the characterization of EMILIN3 deposition in the skin. In addition, to unravel the functions of this protein in skin homeostasis, we generated Emilin3 null mice and provide evidence that EMILIN3 is dispensable for hair follicle growth and maintenance throughout adult life.